Kualitas Pelayanan Terhadap Minat Beli Ulang Pada Event Univlox Lite Night - Sanjaya, Gusti Made Ferry; Paramita, Ratri; Arjaya, Ketut (Journal of Event and Convention Management, 2024)
The research aimed to determine the service quality to repurchase intention on Univlox Lite Night event. The number of the sample of this research was 100 respondents by using non probability sampling technique with purposive sampling. The data was collected throught questionnaires were distributed to visitors who have visited the Univlox Lite Night event. The analysis technique in this research using analysis descriptive by using IBM SPSS program. The result of this research showed service quality “very good” category with an average value of 4,25 and repurchase intention visitor at Univlox Lite Night event was “very good” category with an average value of 4,23. Based on the result of this study, organizer Univlox Lite Night need more explain in detail the information asked by visitor or customers in the social media comment column, and organizer can further convince visitors and build credibility at the event by providing product quality and service quality that matches reality in order to increase repurchase intention and visitors will recommend the product if they feel satisfactions.